DEVELOPING METHODS OF CONTROLLING ELECTRONIC PAYMENT SYSTEMS TO REDUCE FRAUD AND EMBEZZLEMENT PREPARING (World Economics and Finance Bulletin, 2023)
The payment methods sector in France today gives a large place to electronic payment means but must adapt with the arrival of new players, new technologies and an evolution of user expectations. The use of electronic means of payment is well developed in France Businesses and consumers in France today benefit from a diversified range of payment methods characterized by a high level of security and operational continuity, at relatively limited costs. The card is the most used scriptural payment method in terms of number of transactions (49.5% of non-cash payments) and has been growing steadily since 2000 with an average growth rate of 8% per year. While this instrument was designed primarily for physical retail, it is now widely used on the internet and is being used through new payment channels, including the mobile phone. the check is the fourth most used means of payment in the Union, in particular because of the high volumes traded in France, which thus remains the largest market at Union level. In 2013, nearly 71% of checks issued at Union level were in France, far ahead of the United Kingdom (19%). The check accounts for almost 14% of the volume of noncash transactions in France (but only 5% of the amounts). There remains a strong French specificity .
Keywords: French payments industry; manufacturers of payment methods; mobile operators payment service providers